2015
DOI: 10.1155/2015/957043
|View full text |Cite
|
Sign up to set email alerts
|

Chopped Strand/Plain Weave E-Glass as Reinforcement in Vacuum Bagged Epoxy Composites

Abstract: Polymer matrix composites are one of the materials being extensively researched and are gaining a lot of importance due to advantages like high specific strength, greater flexibility in design, and reduced cost of manufacturing. In this study, tensile, flexural, impact, and interlaminar shear strength of chopped strand/plain weave E-glass composites were considered. Composite laminates with different stacking sequence were fabricated using Vacuum Assisted Resin Infusion Moulding (VARIM) technique. Fiber volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In terms of weaving pattern, woven E-glass fibre gives better mechanical properties, compared to chopped strand fibre mat. It was reported that woven E-glass fibre has an impact strength of 415 MPa, while chopped strand E-glass fibre presented 189 MPa [ 70 ].…”
Section: Low Velocity Impact Of Glass Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of weaving pattern, woven E-glass fibre gives better mechanical properties, compared to chopped strand fibre mat. It was reported that woven E-glass fibre has an impact strength of 415 MPa, while chopped strand E-glass fibre presented 189 MPa [ 70 ].…”
Section: Low Velocity Impact Of Glass Compositesmentioning
confidence: 99%
“…Fibre content and fibre arrangement affect the impact properties of not only natural fibre composites, but also of glass fibre composites. A study showed that the maximum impact energy absorbed by composites made from one layer of plain-weave glass fibre and two layers of chopped strand glass mats, with 30% fibre content, was 112.105 kJ/m 2 , while that of composites fabricated from two layers of plain-weave glass fibre and one layer of chopped strand glass mat, with 22% fibre content, was 77.141 kJ/m 2 [ 70 ]. Another study reported that a glass wool fibre reinforced epoxy material with a 40% fibre weight gave the highest impact strength value, which was 0.0862 J/m 2 , compared to 30% and 50% glass wool fibre weight composites, which reached 0.0652 and 0.0421 J/m 2 , respectively [ 71 ].…”
Section: Low Velocity Impact Of Glass Compositesmentioning
confidence: 99%
“…This reduces weight, increases strength and stiffness, and generates a finished part with better mechanical properties (Mohd Yuhazri et al, 2010). Vacuum infusion results in a product with high tensile properties with minimal voids in the finished laminates (Heckadka et al, 2015; Herrera et al, 2019). It is a clean process as it requires neither brushes nor rollers, and therefore there is no spattering.…”
Section: Fiber Volume Fraction and Mechanical Characteristicsmentioning
confidence: 99%
“…The goals of this research is to describe and compare the variation of fibre stacking sequences on quasi-static flexural and creep performance of pGFRP composites. Generally, the pGFRP composite possesses great mechanical strength to resist high load concentration for structural usage [ 61 , 62 ]. Despite many studies focusing on the investigations of FRP composites’ stacking sequences, a comparative study on the effects of stacking sequence on long-term mechanical performance of pGFRP cross arms has still not been fully conducted.…”
Section: Introductionmentioning
confidence: 99%